On How Definitions of Habits Can Complicate Habit Research - De Houwer, Jan (Frontiers in Psychology, 2019)
The core message of this paper is that many of the challenges of habit research can be traced back to the presence of causal elements within the definition of habits. For instance, the idea that habits are stimulus-driven implies that habitual behavior is not causally mediated by goal-representations. The presence of these causal elements in the definition of habits leads to difficulties in establishing empirically whether behavior is habitual. Some of these elements can also impoverish theoretical thinking about the mechanisms underlying habitual behavior. I argue that habit research would benefit from eliminating any reference to specific S-R association formation theories from the definition of habits. Which causal elements are retained in the definition of habits depends on the goals of researchers. However, regardless of the definition that is selected, it is good to be aware of the implications of the definition of habits for empirical and theoretical research on habits.